# (p+q)2-(p-q)2 = ?please solve this ....

2
by anjanaanilrenju
is that (p+q) square or (p+q) * 2 ??
square

2014-08-18T19:42:02+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(P+Q)² - (P-Q)²  =  ?

Left Hand Side LHS  is in the form  A²  - B²  =  (A + B ) ( A - B )

here  A =  P+Q    B is P-Q

So LHS  =  ( P + Q  + P - Q )  [ P + Q  - (P - Q) ]

=  (2 P ) ( p + Q - P + Q )  =  2 P * 2 Q

= 4 P Q
===============================
We can also do this by expanding (P+Q)²

LHS  =  P² + Q² + 2 PQ - [ P² + Q² - 2 PQ ]

= P² + Q² + 2 PQ - P² - Q² + 2 PQ

= 4 PQ

First method is more intelligent method, second method is more hard work, basic principles method.
2014-08-18T23:01:48+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(p+q)2-(p-q)2
= 2p + 2q -2p +2q
= 4q